The Constitution-Conforming Interpretative Judgments: A Comparative Law Analysis - Contreras Segura, Jorge Alvar (2025)
This article examines constitutional interpretation judgments from a comparative law perspective, with particular attention to their application by constitutional courts in civil law legal systems such as Spain, Colombia, Perú, Costa Rica, and Mexico. Through a theoretical and jurisprudential analysis, it presents how these interpretative decisions allow judges to preserve the formal validity of legal provisions, modulating their effects to make them compatible with constitutional principles and values. The study begins with a dogmatic review of the hermeneutical principle of constitutional interpretation, followed by an examination of the typologies and effects of interpretative judgments, and culminates with a functional analysis of their specific application in various jurisdictions. The findings reveal that this technique acts as a balancing mechanism between constitutional supremacy and the democratic principle, avoiding unnecessary normative annulment, correcting structural inequalities, and ensuring the effectiveness of fundamental rights. Overall, the conclusion is that conformity interpretation not only preserves the coherence of the legal system but also projects a transformative reading of the law from the paradigm of the constitutional state.